Mevo lectin specificity toward high-mannose structures with terminal αMan(1, 2)αMan residues and its implication to inhibition of the entry of Mycobacterium tuberculosis into macrophages. (1st April 2021) - Sivaji, Nukathoti; Harish, Nikitha; Singh, Samsher; Singh, Amit; Vijayan, Mamannamana; Surolia, Avadhesha
Abstract: Mannose-binding lectins can specifically recognize and bind complex glycan structures on pathogens and have potential as antiviral and antibacterial agents. We previously reported the structure of a lectin from an archaeal species, Mevo lectin, which has specificity toward terminal α1, 2 linked manno-oligosaccharides. Mycobacterium tuberculosis expresses mannosylated structures including lipoarabinomannan (ManLAM) on its surface and exploits C-type lectins to gain entry into the host cells. ManLAM structure has mannose capping with terminal αMan(1, 2)αMan residues and is important for recognition by innate immune cells. Here, we aim to address the specificity of Mevo lectin toward high-mannose type glycans with terminal αMan(1, 2)αMan residues and its effect on M. tuberculosis internalization by macrophages. Isothermal titration calorimetry studies demonstrated that Mevo lectin shows preferential binding toward manno-oligosaccharides with terminal αMan(1, 2)αMan structures and showed a strong affinity for ManLAM, whereas it binds weakly to Mycobacterium smegmatis lipoarabinomannan, which displays relatively fewer and shorter mannosyl caps. Crystal structure of Mevo lectin complexed with a Man7D1 revealed the multivalent cross-linking interaction, which explains avidity-based high-affinity for these ligands when compared to previously studied manno-oligosaccharides lacking the specific termini. Functional studies suggest that M. tuberculosis internalization by the macrophage was impaired by binding of Mevo lectin to ManLAM present on the surface of M. tuberculosis . Selectivity shown by Mevo lectin toward glycans with terminal αMan(1, 2)αMan structures, and its ability to compromise the internalization of M. tuberculosis   in vitro, underscore the potential utility of Mevo lectin as a research tool to study host-pathogen interactions.